2009
DOI: 10.7863/jum.2009.28.7.871
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Targeted Methotrexate Delivery to the Rabbit Brain via Magnetic Resonance Imaging-Guided Focused Ultrasound

Abstract: Magnetic resonance imaging-guided FUS can disrupt the BBB reversibly and deliver IV administered MTX to targeted brain locations; it brings about a greater than 10-fold increase in the drug level and is much more effective (approximately 3.7-fold) than drug delivery through the ICA without sonication. This may facilitate the development of improved treatment methods for central nervous system disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 18 publications
1
64
0
1
Order By: Relevance
“…They observed the extravasated red blood cells and tissue necrosis by H&E staining (11,15,21), DNA fragmentation and apoptotic bodies in the cells by TUNEL staining (5,11,21), major ischemic changes by vanadium acid fuchsin-toluidine blue staining (5,14), and the occurrence of an inflammatory response by fluorescein isothiocyanate-coated CD-11b fluorescent antibody labeling and Prussian blue staining (30). In some studies, lesions induced by focus ultrasound were also examined histologically by electron microscopy (19,21,31).…”
Section: Nonhemorrhagic Vs Biosafety Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed the extravasated red blood cells and tissue necrosis by H&E staining (11,15,21), DNA fragmentation and apoptotic bodies in the cells by TUNEL staining (5,11,21), major ischemic changes by vanadium acid fuchsin-toluidine blue staining (5,14), and the occurrence of an inflammatory response by fluorescein isothiocyanate-coated CD-11b fluorescent antibody labeling and Prussian blue staining (30). In some studies, lesions induced by focus ultrasound were also examined histologically by electron microscopy (19,21,31).…”
Section: Nonhemorrhagic Vs Biosafety Conditionsmentioning
confidence: 99%
“…This increase in BBB permeability can be detected by contrast-enhanced MRI using gadolinium-based (8,9) or iron oxide-based contrast agents (10) or by single-photon emission computed tomography with 99m Tc-based radiotracers (11). Using these imaging methods to guide FUS sonication, BBB at the targeted brain regions can be disrupted accurately, facilitating the delivery of diagnostic or therapeutic agents (12)(13)(14)(15)(16)(17).Although FUS sonication is promising in facilitating drug delivery across BBB, increasing concerns have been raised regarding its potential adverse effects on the brain. Indeed, FUS sonication could damage the brain tissue via FUS-induced edema, hemorrhage, ischemia, and apoptosis (10,18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery of the BBB functionality has been reported to be between 6 and 24 h for small tracer molecules such as gadolinium, 61,62 and by 12 h the levels of tight junctional proteins have been restored. 63 Contrast enhanced MRI has shown that once the BBB is closed following FUS, the barrier remains impenetrable up to 4 weeks later.…”
Section: ■ Cellular Mechanisms Of Fusmentioning
confidence: 99%
“…53 For example, MRgFUS delivered intravenous methotrexate to the brains of healthy rabbits at concentrations 13 times higher than intravenous methotrexate delivery alone (p < 0.01) and more than 3 times higher than methotrexate delivery via the internal carotid artery without MRgFUS (p < 0.01). 40 Thus, MRgFUS can reduce side effects of chemotherapeutic agents by requiring a lower systemic dose to reach a desired brain tumor tissue concentration. MRI guidance allows for not only identification of the lesion to be targeted but also dynamic feedback on the extent of BBB disruption via contrast leakage.…”
Section: Mrgfus and Microbubbles Focally Disrupt The Bbbmentioning
confidence: 99%